2007
DOI: 10.1016/j.pnpbp.2007.08.028
|View full text |Cite
|
Sign up to set email alerts
|

How to make a rat addicted to cocaine

Abstract: Procedures have been developed which provide extremely stable patterns of cocaine selfadministration in rats and these have been useful in lesion and drug pretreatment studies aimed at understanding the neurobiology of cocaine reinforcement. The issue now is whether studying the neurobiology of reinforcement is the same as studying the neurobiology of addiction. If the goal is to understand a progressive and deteriorating disorder, then the self-administration procedures should model specific aspects of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
115
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 77 publications
3
115
0
1
Order By: Relevance
“…Moreover, the use of extended access to cocaine (ie, X6 h) is known to specifically model specific neurobehavioral features of addiction, such as persistent alterations in cognitive functions (Briand et al, 2008;George et al, 2007), increased motivation for cocaine (Paterson and Markou, 2003), and escalation in drug intake (Ahmed and Koob, 1998). Repeated periods of forced abstinence were introduced to reduce the acute toxic effects of the drug and to ensure sustained motivation to self-administer high doses of cocaine (Roberts et al, 2007). Although the total cocaine intake achieved with the present protocol is higher than that observed with short-access paradigms, the values attained are sufficiently distant from the limit of acute toxicity (Mantsch et al, 2004;Wee et al, 2007), which explains the lack of lethality observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the use of extended access to cocaine (ie, X6 h) is known to specifically model specific neurobehavioral features of addiction, such as persistent alterations in cognitive functions (Briand et al, 2008;George et al, 2007), increased motivation for cocaine (Paterson and Markou, 2003), and escalation in drug intake (Ahmed and Koob, 1998). Repeated periods of forced abstinence were introduced to reduce the acute toxic effects of the drug and to ensure sustained motivation to self-administer high doses of cocaine (Roberts et al, 2007). Although the total cocaine intake achieved with the present protocol is higher than that observed with short-access paradigms, the values attained are sufficiently distant from the limit of acute toxicity (Mantsch et al, 2004;Wee et al, 2007), which explains the lack of lethality observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…By employing different SA patterns, experimenters have been able to reproduce several hallmark features of drug addiction, including compulsive drug seeking (Vanderschuren and Everitt, 2004), uncontrolled drug use (Ahmed and Koob, 1998), and increased motivation to SA the drug (Paterson and Markou, 2003). These features make these models an experimental tool of excellent face validity to investigate the neuroplastic events associated with voluntary drug intake (Roberts et al, 2007). However, specific clinical correlates of cocaine addiction, such as the blunted DA responsivity of striatal areas observed in PET studies (Volkow et al, 1993;Martinez et al, 2004), do not appear to be adequately modeled by traditional short-term, limited-access cocaine SA paradigms, where instead 'sensitized' (ie, increased) dopaminergic responses are typically observed (Narendran and Martinez, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, and for many decades, the majority of preclinical studies have examined cocaine self-administration behavior under short access (ShA) conditions (1-2 h/day), which results in relatively low and stable levels of intake. In contrast, the goal of newer addiction paradigms is to more fully capture features that are critical to human cocaine addiction, such as excessive drug use and an enhanced subsequent motivation to use the drug (Ahmed, 2012;Roberts et al, 2007). This latter characteristic, an enhanced level of motivation to obtain the drug as compared with baseline or ShA controls, has been used to define the development of an addicted phenotype (Roberts et al, 2007;Lynch and Taylor, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the goal of newer addiction paradigms is to more fully capture features that are critical to human cocaine addiction, such as excessive drug use and an enhanced subsequent motivation to use the drug (Ahmed, 2012;Roberts et al, 2007). This latter characteristic, an enhanced level of motivation to obtain the drug as compared with baseline or ShA controls, has been used to define the development of an addicted phenotype (Roberts et al, 2007;Lynch and Taylor, 2004). The use of extended access (ExA) conditions (6-24 h/day) coupled with a protracted abstinence period (7 days or more) appear to be necessary for inducing this phenotype in animals.…”
Section: Introductionmentioning
confidence: 99%